Optimizing Entrepreneurship Through Product Upgrading for The Kerinjing Village Community in Tanjung Raja District, Ogan Ilir Regency, South Sumatera - Sari Mutiara Aisyah; Abdul Halim; Indra Tamsyah; Gunawan Lestari Elake; Yuniarsih Manggarsari (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
This community service program has the aim of increasing community capacity in the context of entrepreneurship by maximizing the potential of the village and its human resources. Kerinjing village has high calamansi fruit production potential, but this potential has not been maximized by the villagers. This is the reason why this village is chosen as an object of this program. The assistance was carried out through several stages such as initial preparation and village mapping, training in two phases, and evaluation. This mentoring was carried out for 15 days, by providing the education and understanding about the potential of the area, which was then continued with the introduction of processing calamansi fruit into syrup products that have a selling value with a clean, simple and inexpensive production process. In addition, this Program also introduces optimizing product with added value through trademark, labelling product and attractive packaging. The result of the implementation was that it could run very well, the ability of the production process and the knowledge of the community also increases. This community service program is expected to be an opportunity that can be used by villagers to maximize the potential of the village, provide new and promising business opportunities that are correlated with improving the economy of rural communities, especially during a pandemic era like today.